Species Diversity of Gastropods in the Mangrove Forest of Pangpang Bay Ijen Geopark, Banyuwangi Indonesia - Setiawan, Rendy; Wimbaningrum, Retno; Sulistiyowati, Hari; Siddiq, Arif Mohammad; Rani, Cynthia; Baraas, Abdillah (Jurnal Kelautan Tropis, 2024)
Gastropods are invertebrate animals from the phylum Mollusca which have soft bodies and most of them have shells. The Pangpang Bay mangrove forest has a muddy substrate type and contains a lot of organic matter as a food source. This research was conducted in October - December 2022 at the Pangpang Ijen Geopark Bay. The area of the research area is about 900 meters2 with a total plot size of 1x1 m totaling 99 plots. The gastropod data collection method uses the systematic plot transect method. The recorded data contains the local name/type/type code, the number of species, and the number of individuals of each type. Data on abiotic environmental factors which include temperature, pH, and salinity are determined by the range of values and the type of substrate. Further data analysis was carried out by determining the species composition of gastropods by calculating the Shannon-Wiener (H') species diversity index. The results showed that there were 20 types of gastropods with members from 11 genus and 7 families. The results showed that the gastropod diversity index at the study site is in the medium category with a value of 1.95. The conclusion of this study is the diversity of species found in the mangrove forest of Pangpang Ijen Geopark Bay as many as 20 species. The value of diversity of gastropod species in the Pangpang Ijen Geopark Bay mangrove forest is in the moderate category because there are quite a lot of species found and only one species dominates.